Dendrochronological record of soil creep and landslide activity – the comparison of tree-ring eccentricity and compression wood (examples from the Kamienne Mts., Poland) - Sitko, Katarzyna; Wistuba, Małgorzata; Malik, Ireneusz; Krąpiec, Marek; Yu, Ruide; Zhang, Haiyan (Geology, Geophysics and Environment, 2022)
Forested mountain slopes can be simultaneously affected by soil creep and landslide activity, both of which cause the tilting of tree stems, with the result that their dendrochronological record of tree-ring eccentricity and compression wood is potentially similar. There is a need to identify similarities and differences in these records and thus our research aimed to compare patterns of eccentricity and compression wood developed by trees under the impact of soil creep and landslides. We sampled trees growing on a landslide and creeping slopes in the Kamienne Mts., with 21 Norway spruce trees were sampled on each site. We found several main differences between the dendrochronological record of landslide activity and soil creep. On the landslide we found larger number of dendrochronological events, stronger and more variable eccentricity and a similar number of upslope and downslope events. On creeping slopes, upslope eccentricity events predominate, and the number of eccentricity events dated in all trees increases in time. We also compared the utility of eccentricity and compression wood for dating mass movements. They differ in their sensitivity to stem tilting. Thus, in analyses of landslide activity and soil creep activity, it is recommended to include both wood anatomy features.